GE_GERICHTE C/17754/2014 vom 12. Februar 2016 - GE Cour de justice (2016)
DÉFAUT(CONTUMACE); BAIL À LOYER; CHOSE MOBILIÈRE; DEMEURE DU DÉBITEUR; RÉSILIATION | CPC.147; CPC.223.2; CPC.234.1; CPC.317.1.b